Construct the quadratic that has one root (1/3)+square root (2/3).
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
The roots of a quadratic equation, if irrational, are found as pairs. Here we have one roots as 1/3 + sqrt 2/3, the other root will be 1/3...
(The entire section contains 76 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- square root(x+square root(1-x))+square rootx=1. What is x?
- 1 Educator Answer
- Solve the equation square root(x^2-5)-square root(x^2-8)=1
- 1 Educator Answer
- Given the fraction E(x)=(x^3-3x-2)/(x^3+1+3x^2+3x). Solve the equation E(x)=square root 3-square...
- 1 Educator Answer
- Find the product of roots of quadratic equation if |x1-x2|=1 and x^2=2x-m.
- 1 Educator Answer
- Solve the equation 1/2^(x^2-1)=square root(16^x).
- 1 Educator Answer
If one root of a quadratic is (1+sqrt2)/3, then it's conjugate, (1-sqrt2)/3, is also a root for the quadratic.
We'll use the formula of a quadratic:
x^2 - Sx + P = 0
S is the sum of the roots.
P is the product of the roots.
Since we know both roots, we'll determine their sum and product to create the quadratic.
x1 + x2 = S = 1/3 + (sqrt2)/3 + 1/3 - (sqrt2)/3
We'll eliminate like terms:
x1 + x2 = S = 2/3
The product is:
P = x1*x2 = (1+sqrt2)(1-sqrt2)/9
The numerator represents the difference of 2 squares:
P = (1-2)/9
P = -1/9
We'll create the quadratic: x^2 - 2x/3 - 1/9 = 0
We'll multiply by 9 the quadratic:
9x^2 - 6x - 1 = 0
The final form of the quadratic is: 9x^2 - 6x - 1 = 0.
Student Answers